Waldenström macroglobulinaemia presenting as tingling ulcers on the feet - Isabelle Fischer; Delwyn Dyall-Smith; Birgit Peters; Wilhelm Stolz; Brigitte Coras-Stepanek (Mattioli1885, 2013)
A 56-year-old man presented with tingling ulcers on the feet. On further skin examination, papules on the knees were observed. Biopsies revealed extravascular eosinophilic deposits of IgM, and Waldenström macroglobulinaemia was diagnosed. The skin manifestations have resolved with chemotherapy. Peripheral neuropathy and storage papules are rare manifestations of Waldenström's macroglobulinaemia.